The PDGF-BB-SOX7 axis-modulated IL-33 in pericytes and stromal cells promotes metastasis through tumour-associated macrophages - Yunlong Yang (Nature Portfolio, 2016)
Elevated IL-33 levels have been correlated with metastasis and poor prognosis. Here the authors show in mouse tumour xenograft models that PDGF-BB produced by tumour cells induces IL-33 via Sox7 in tumour pericytes, and IL-33 promotes metastasis through its effects on tumour-associated macrophages.